Inculturation: with special reference to the Catholic Church in Lesotho and to liturgy - Moloi, Ernest Thabang (Department of Religious Studies, 2024)
Biological extinction rates have escalated by as much as 1000 times the background extinction rate over the last 1500 years, causing concern over the long-term survival of many species. Avian extinctions since 1600 have been well documented relative to other taxa, as have current levels of avian threat. This study analyses avian extinctions post-1600 and current threats in an attempt to develop some predictive capacity about which avian taxa should be awa,rded the highest conservation priority. Analyses performed include examinations of the causes of avian extinction and threat, geographical location of extinct and threatened species, prehistoric and historical extinction rates, endemicity, migration, bird body size and phylogenetic diversity. An analysis dealing with historical and phylogenetic aspects of endangered and critically threatened species was performed, from which the world's most threatened species were identified. Factors which were the primary cause of historical extinctions are generally not the primary factors threatening today's extant avifauna. Whilst introduced predators and exploitation were primary causes of historical extinctions, habitat destruction poses the greatest threat to extant birds. Species predisposed to extinction typically have restricted ranges, and, compounded by habitat loss, these ranges are becoming more restricted. This has resulted in mainland-dwelling species becoming as prone to extinction as island-dwelling species have been historically. IIltroduced predators, however, do still threaten many of the world's most threatened species and their potential effects are highlighted in the phylogenetic analysis. Already, many extinctions may be inevitable over the next 25 years as a result of habitat loss. The magnitude of extinctions across all animal and plant species in the next few decades could be comparable with that of previous mass extinctions unless immediate conservation action is taken. However, future conservation efforts will have to be prioritized, and this study is intended as a contribution towards such a prioritization exercise.